Investigation on tool properties for the production of components with micro textured surfaces. Issue 1 (1st May 2022) - Reck, M; Merklein, M
Abstract: Defined surface micrcotextures offer potential for the friction reduction in elastohydrodynamic contacts and can thus increase the energy efficiency of technical systems. The production of prostheses, where microtextured surfaces can provide anti-bacterial effects is another application area. To manufacture these components economically in large quantities, forming processes are to be aimed at. Since lightweight parts are crucial in most application areas, the forming of sheet metal is the subject of current research. A major aspect of the presented investigation is the behavior of tool materials for the production of such microtextured sheet metal parts. Applying microtextures of varying geometries to the tools is a key challenge. Limitations in the accuracy of electrical discharge machining processes for the fabrication of micro cylinders, prisms and cuboids are therefore analyzed on the high-speed steels 1.3343 and 1.3244. In addition, the tool surfaces are characterized regarding their friction properties with case hardening steel as a contact partner. In this paper, the tool friction is analyzed for the steel 1.7131 (16MnCr5) with an initial sheet thickness of t0 = 2.4 mm, which is often utilized for high-wear applications due to its high strength and toughness. In this context, the friction behavior of the wax-containing lubricant Beruforge 150 DL made for bulk forming processes is compared with zinc-free high-performance lubricants Raziol CLF 65-400 of varying viscosity.